Discrete stochastic port-Hamiltonian systems. (March 2022) - Cordoni, Francesco Giuseppe; Di Persio, Luca; Muradore, Riccardo
Abstract: The present paper aims at defining discrete stochastic port-Hamiltonian systems (SPHS). We introduce a suitable definition of discrete SPHS based on symplectic variational integrators. By properly choosing the collocation points for discrete-time SPHS we are able to approximate a continuous SPHS. Moreover, under suitable assumptions on the Hamiltonian of the system, we guarantee energy conservation, which is a key property in the standard PHS framework. Numerical examples are provided to show the goodness of the proposed method.